Economic Stability in Balkans the Role of Greece - Vergopoulos, Kostas (Études helléniques / Hellenic Studies, 2000)
According to certain well-established laws of geopolitics, the European continent has long been obsessed by intensities and waves of uncertainty that moved from east to west and north to south. Stability in Northern Europe when compared to Southern Europe continues to be exemplary and unsurpassable. The same applies to the west of the continent, in comparison to the east. It is also well known that the Balkans, as the crossroads of explosive geopolitical influences, have become the ‘boiling pot’ of Europe. Southeastern Europe sits exactly in the eye of the storm, situated between two destabilizing influences and running through Europe from south and the east. Two sub-areas of that region are permanent sources of disruption. The first, to the east of the Mediterranean, is the long lasting and unresolvable Middle Eastern issue between Israel and neighboring Arab populations. The second, to the north of the eastern Mediterranean, is formed by the Balkans and Turkey. This brief review introduces an examination of Balkan stability and Greece’s geopolitical role.